KOMUNIKASI INSTRUKSIONAL PELATIH DALAM KEGIATAN LATIHAN ATLET CABANG OLAH RAGA DRUMBAND PERSATUAN DRUM BAND INDONESIA PROVINSI RIAU - Wirahayu Diannisa; Hevi Susanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Indonesian Drum Band Association (PDBI) organization is under the auspices of the Ministry of Youth and Sports of the Republic of Indonesia. In Riau Province, there are only 4 districts and cities that have active PDBI management, namely Bengkalis, Meranti Islands, Rokan Hilir, and Pekanbaru City. There are around 500 units of marching bands under the auspices of PDBI Riau Province such as Dang Merdu Marching Corps, Marching Band Bahana Cendana Kartika Duri and Rumbai Units, Drum Corps Sang Surya, Andam Dewi Marching Band, Marching Band Gita Wibawa Praja, and others. PDBI forms a drumband unit that is focused on becoming drumband athletes. The purpose of this research is to find out the methods used during the training process, the credibility of the coaches of drumband athletes, and to find out what obstacles are experienced in the training activities of drumband athletes. This research uses qualitative research methods. The subjects in this study were the head of the organizational field, coaches, and athletes selected by purposive technique. Data collection techniques consist of observation, interviews, and documentation. While the data analysis technique uses interactive analysis according to Miles and Huberman. The data validity technique used in this research is the extension of participation and triangulation. The results showed that the coach's instructional methods in training are divided into command methods, practice/practice methods, and training methods with friends. The credibility of the coach can be seen from the experience, achievements, certificates achieved, and the athlete's trust in the coach. Instructional communication barriers in athlete training are differences in schedules for each athlete, lack of resources to facilitate training, and time adjustments with different athlete activities. The results of this study can be a reference material for the drumband PDBI Riau Province to be able to improve the discipline of its athletes.